2013
DOI: 10.1007/s13105-013-0300-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings on the influence of FTO rs9939609 and MC4R rs17782313 polymorphisms on resting energy expenditure, leptin and thyrotropin levels in obese non-morbid premenopausal women

Abstract: Given that leptin, ghrelin and thyrotropin play a major role in the regulation of resting energy expenditure (REE) and that the FTO rs9939609 and the MC4R rs17782313 polymorphisms have been proposed to affect energy homeostasis, we hypothesized that both polymorphisms are associated with REE and that these relationships can be mediated by leptin, ghrelin and thyrotropin in obesity. Therefore, the present study aimed to examine the relationships between FTO rs9939609 and the MC4R rs17782313 with REE, leptin, gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It is plausible that FTO risk allele can increase the level of serum leptin via increasing the BF and BMI. FTO rs9939609 polymorphism is reported to be associated with REE [29]. The leptin also plays an important role in the regulation of resting energy expenditure (REE).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that FTO risk allele can increase the level of serum leptin via increasing the BF and BMI. FTO rs9939609 polymorphism is reported to be associated with REE [29]. The leptin also plays an important role in the regulation of resting energy expenditure (REE).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a multicenter trial in Europe showed strong association with severe obesity in bariatric patients ( p = 9.2 × 10 − 8 , OR = 1.47) as well [ 35 ]. The association of the risk allele “A” with higher leptin to fat mass ratio, higher levels of thyrotropin and lower resting energy expenditure is a likely explanation for its predisposition to increased obesity risk [ 36 ]. However, there have been studies in African American and Chinese Han population that show no association of the “A” allele with higher BMI risk [ 27 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…FTO risk alleles have been associated with changes in circulating levels of the appetite regulating hormones leptin and ghrelin. Several papers have shown that FTO risk allele is associated with increased circulating leptin levels [ 40 47 ]. However, this association appears to be mediated via increased adiposity, as in several studies the association disappears when correcting for BMI [ 42 , 44 46 ].…”
Section: Regulation Of Fto Expressionmentioning
confidence: 99%